Intracranial mesenchymal tumors with FET‐CREB fusion are composed of at least two epigenetic subgroups distinct from meningioma and extracranial sarcomas. (25th November 2021) - Sloan, Emily A.; Gupta, Rohit; Koelsche, Christian; Chiang, Jason; Villanueva‐Meyer, Javier E.; Alexandrescu, Sanda; Eschbacher, Jennifer M.; Wang, Wesley; Mafra, Manuela; Ud Din, Nasir; Carr‐Boyd, Emily; Watson, Michael; et al.
Abstract: 'Intracranial mesenchymal tumor, FET‐CREB fusion‐positive' occurs primarily in children and young adults and has previously been termed intracranial angiomatoid fibrous histiocytoma (AFH) or intracranial myxoid mesenchymal tumor (IMMT). Here we performed genome‐wide DNA methylation array profiling of 20 primary intracranial mesenchymal tumors with FET‐CREB fusion to further study their ontology. These tumors resolved into two distinct epigenetic subgroups that were both divergent from all other analyzed intracranial neoplasms and soft tissue sarcomas, including meningioma, clear cell sarcoma of soft tissue (CCS), and AFH of extracranial soft tissue. The first subgroup (Group A, 16 tumors) clustered nearest to but independent of solitary fibrous tumor and AFH of extracranial soft tissue, whereas the second epigenetic subgroup (Group B, 4 tumors) clustered nearest to but independent of CCS and also lacked expression of melanocytic markers (HMB45, Melan A, or MITF) characteristic of CCS. Group A tumors most often occurred in adolescence or early adulthood, arose throughout the neuroaxis, and contained mostly EWSR1 ‐ ATF1 and EWSR1 ‐ CREB1 fusions. Group B tumors arose most often in early childhood, were located along the cerebral convexities or spinal cord, and demonstrated an enrichment for tumors with CREM as the fusion partner (either EWSR1 ‐ CREM or FUS ‐ CREM ). Group A tumors more often demonstrated stellate/spindle cell morphology and hemangioma‐like vasculature, whereas Group B tumors more often demonstrated round cell or epithelioid/rhabdoid morphology without hemangioma‐like vasculature, although robust comparison of these clinical and histologic features requires future study. Patients with Group B tumors had inferior progression‐free survival relative to Group A tumors (median 4.5 vs. 49 months, p = 0.001). Together, these findings confirm that intracranial AFH‐like neoplasms and IMMT represent histologic variants of a single tumor type ('intracranial mesenchymal tumor, FET‐CREB fusion‐positive') that is distinct from meningioma and extracranial sarcomas. Additionally, epigenomic evaluation may provide important prognostic subtyping for this unique tumor entity. Abstract : We studied the epigenomic landscape of intracranial mesenchymal tumor with FET‐CREB fusion, an emerging CNS tumor entity that occurs primarily in children and young adults. These tumors resolved into two epigenetic subgroups with divergent clinical outcomes that were distinct from meningiomas and all analyzed extracranial sarcomas.